A photographic food atlas with portion sizes of commonly consumed foods in Accra, Ghana - Folson, Gloria; Bannerman, Boateng; Ador, Gabriel; Atadze, Vicentia; Akoto, Saudatu; Asante, Stephen; Abbeyquaye, Joseph; Anang-Tetteh, Audrey; Guri, Erica; Ibrahim, Gabriel; Alhassan, Jamil; Tetteh, Matilda; et al. (International Food Policy Research Institute, 2022)
This Food Atlas provides a photograph series of 68 meals commonly consumed by adolescent girls in Accra, Ghana. It consists of pictures of four portion sizes per meal, including weights.